PLURIPOTENT STEM CELLS AND CELLULAR INNOVATIONS: ADVANCING REGENERATIVE MEDICINE (World Bulletin of Public Health, 2025)
Human pluripotent stem cells (hPSCs) hold immense promise for regenerative medicine, with therapies for over 14 diseases and injuries advancing toward clinical trials. Applications include differentiating hematopoietic stem cells for blood disorders, generating liver and kidney organoids for organ failure, and leveraging exosomes to combat skin aging and inflammation. Complementary advances in structural biology, such as cryo-electron microscopy (cryo-EM) and cryo-electron tomography (cryoET), provide high-resolution insights into macromolecular interactions in situ, while microphysiological systems (MPSs) mimic organ physiology using hPSC-derived cells. Cell mechanics, including membrane dynamics and fibroblast heterogeneity (e.g., 15-30% of heart cells), further inform differentiation and tissue engineering. This review synthesizes hPSC-based therapies, exosome applications, structural biology, MPSs, cell mechanics, and tissue engineering, emphasizing their interconnected roles in addressing challenges like tumorigenicity, immunogenicity, and system complexity in regenerative medicine